Körper im höfischen Gespräch Die Briefe Liselottes von der Pfalz im Kontext des höfischen Kommunikationsideals - Bovt, Aleksandra (Universitätsverlag Göttingen, 2020)
The extensive collection of correspondences of Elisabeth Charlotte, Duchesse d'Orléans (known as Liselotte von der Pfalz), sister-in law of Louis XIV, is one of the few remaining sources with exceptional insight into the life at the court of the Sun King. Her letters contain numerous lively and witty descriptions of the appearances and bodily practices of the contemporaries she met there - descriptions that range from subtle anecdotes to scatological jokes. Especially the latter, sometimes paired with strong language, have led various scholars to believe that her writing style was not in accordance with the refined communication culture at the court. The perception of Liselotte's writing style, characterized by literary and theatrical allusions, repartee, and a tendency towards detailed description of courtly life, seems to be dominated by a stereotypical classification of Liselotte as a "unrefined German" contrasted with the gallantry of the French. This study contradicts this assumption by analysing whether and to what extent the writing about the body in Liselotte's letters follows the rules described in the handbooks on courtly communication of the Early Modern Period.